The Sterol Trafficking Pathway in Arabidopsis thaliana - Kumar, Krishna; Gibbs, Holly C.; Yeh, Alvin T.; Griffing, Lawrence R. (Frontiers in Plant Science, 2021)
In plants the trafficking mechanisms by which sterols move through the plant and into target cells are unknown. Earlier studies identified endosomes as primary candidates for internalization of sterols in plants, but these results have come into question. Here, we show that in elongating root cells, the internalization of sterol occurs primarily by a non-endocytic mechanism. Added fluorescent sterols (dehydroergosterol, DHE, and Bodipy-cholesterol, BCh) do not initially label endosomes identified by fluorescent protein markers or by internalized FM4-64. Instead, the nuclear envelope, an organelle not associated with the endocytic pathway but part of the endoplasmic reticulum (ER), becomes labeled. This result is supported by experiments with the inducible over-expression of auxillin-2-like protein (AUX2 line), which blocks most endocytosis upon induction. Internalization and nuclear envelope labeling still occur in induced AUX2 cells. Longer term incubation in root cells labels the oil body, a site involved in sterol storage. In hypocotyl cells, other organelles, such as the vacuole membrane, plasmodesmata, and putative ER exit sites label. Although the first site of localization, the nuclear envelope, is part of the ER, other domains of the ER do not accumulate the label. The trafficking pathway differs from vesicular endocytosis and points toward different pathways of sterol transport in different cell types and the potential importance of sterol transport mediated by other mechanisms, such as endoplasmic reticulum-plasma membrane contact sites and cytoplasmic transport.